«EFFICIENCY OF MULTI-CUT SHAFT MACHINING ON A LATHE» - Tadaeva Elena Vladimirovna (Galaxy International Interdisciplinary Research Journal, 2022)
The article describes the methods of processing stepped shafts on lathes, the choice of method and cutting tool, the method of processing stepped shafts using thrust cutters is described in detail.